Uncovering genetic changes underlying adaptation in southern African dwarf chameleons (Bradypodion) - Taft, Jody M. (University of the Witwatersrand, Johannesburg, 2024)
Natural selection acting on the available range of phenotypes in a population will favour alleles beneficial to an organism’s fitness, resulting in adaptation. Characterizing patterns of adaptive genetic variation in wild populations is a fundamental first step toward understanding the potential for adaptation in response to selection. With recent advances in sequencing technology, the increased availability of high-quality genomic resources has made efforts to identify loci under selection across the genome more tractable. As a result, there is a growing body of research challenging the notion that adaption takes place over deep evolutionary timescales, with evidence of rapid adaptation occurring in a range of taxa. Examples of rapid adaptation are rife within reptiles, particularly in response to contemporary environmental changes such as urbanization. Despite this, insights into the genetic architecture of adaptation in reptiles remain limited as appropriate genomic resources are currently lacking. The southern African dwarf chameleons, Bradypodion, are the most recently diverged lineage in Chamaeleonidae. These arboreal lizards are well known for their high capacity for adaptation, especially in response to environmental change. Bradypodion are known to have undergone rapid diversification linked to habitat specialization resulting in the emergence of few convergent phenotypes, or ecomorphs, across the genus. These lizards occupy a variety of habitat types, from closed-canopy forests to open-canopy habitats such as grasslands, but are also known to occur within urban environments. As ecomorphs of various Bradypodion species display phenotypic convergence in similar habitat types, populations may also converge phenotypically in urban habitats. However, the underlying genetic architecture of these phenotypes remains unknown for Bradypodion, further constrained given the absence of appropriate genomic resources for these lizards. To facilitate insights into the genetic architecture underlying adaptation in Bradypodion, two de novo assembled whole genomes were produced using Pacific Biosciences long-read sequencing data. These assemblies are among the highest-quality squamate genomes published to date. In addition, coalescent analyses of these assemblies indicated that historical changes in effective population size correspond to notable shifts in the southern African environment. Furthermore, the high-quality annotations of both Bradypodion genome assemblies were generated and used to describe the genetic feature landscapes and evaluate the gene family evolution of Bradypodion. Findings indicated that expanded gene families within this genus are likely the result of responses to changing environmental conditions, facilitating the diversification of Bradypodion. In addition, differences in gene family composition at the species level provide insights into underlying genetic pathways resulting in adaptive traits possibly promoting ecomorph divergence across the genus. Lastly, to detect loci under selection, population structure and genetic diversity were assessed in five species of Bradypodion known to have populations in natural and urban habitats using a pairwise comparative approach. While there is evidence of allele frequency differentiation between urban and natural populations, it is uncertain that this is due to selection pressures experienced by the urban population. While links between genes containing outlier loci and the phenotypic traits known to be associated with adaptation in urban habitats are made, it is recommended that these genes be used as candidates for targeted gene modification to evaluate the phenotypes generated by those modifications and contrasted with phenotypes present in urban populations. This thesis provides insights into the mechanistic genomic basis of adaption in Bradypodion. The high-quality genomes and annotations produced here will hopefully serve as a resource for further assessments of genetic adaptation in chameleons and reptiles more broadly. Furthermore, these findings present a framework from which to formulate robust hypotheses to assess candidate genes presented here as likely underlying adaptive phenotypes in urban populations
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science ,School of Animal, Plant and Environmental Sciences University of the Witwatersrand, Johannesburg, South Africa, 2024
Keywords: Natural selection; Genomic resources; Rapid adaptation; Genetic architecture; UCTD; SDG-3: Good health and well-being